Fulfilling Malay literature learning outcomes and teacher difficulty - Ahmad Nazri, Abdullah; Noor Asliza, Abdul Rahim; Suhaidah, Said; Zuhairah, Idrus (International Islamic University Malaysia (IIUM), 2008)
Organized by International Islamic University Malaysia (IIUM), 3rd - 5th March 2008 at Hotel Legend, Kuala Lumpur.